RETRACTED: Possible consequences of nonstationary loads on the durability of welded joints for low-alloy steel fittings - Moskalev L.N.; Ponikarov S.I. (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001